I mosaici di Piazza Anita Garibaldi a Ravenna: ipotesi di restauro virtuale - Monti, Mariapaola; Maino, Giuseppe (Archeomatica, 2013)
During the excavations carried out in summer 2011 by Hera (a multiutility company that deals with the management of water, energy and waste in Emilia Romagna) in Piazza Anita Garibaldi in Ravenna for the making of new underground waste containers for the separate collection, five rooms decorated with mosaic floors were found, probably dating to the early Roman Empire (I-II century A.D.). The mosaics were removed for restoration and musealization, however - given the size of the lacunae – it would not be possible to reintegrate them in a traditional restoration without creating arbitrary reconstructions. For this reason we opted for a digital reconstruction of the lacunae, making some virtual restoration hypothesis for the recovered mosaics;by this way it is possible to grasp the trend of the figuration how it could have been in the past.